2005
DOI: 10.1021/ja051233z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Physical Properties, Multitemperature Crystal Structure, and 20 K Synchrotron X-ray Charge Density of a Magnetic Metal Organic Framework Structure, Mn3(C8O4H4)3(C5H11ON)2

Abstract: A new magnetic metal organic framework material has been synthesized, Mn3(C8O4H4)3(C5H11ON)2, 1. Magnetic susceptibility measurements from 2 to 400 K reveal anti-ferromagnetic ordering at approximately 4 K and a total magnetic moment of 6.0 micro(B). The magnetic phase transition is confirmed by heat capacity data (2-300 K). The crystal structure is studied by conventional single-crystal X-ray diffraction data at 300, 275, 250, 225, 200, 175, 150, 125, and 100 K, and synchrotron data at 20 K. There is a phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…The Mn1-O bond lengths are in agreement with distances reported earlier for similar coordination environments. [18] The coordination angles, ranging from 86.02 (13) to 93.98(13)°( see Table 2), are close to 90°, the ideal value for a perfect octahedron. Mn1 is bridged to Mn2 and to its symmetryrelated counterpart Mn2a [the distance Mn1-Mn2 is 3.6024(10) Å], generating a trinuclear cluster.…”
Section: [Mn 3 (Atpa) 3 (Dmf) 4 ] (2)mentioning
confidence: 61%
See 2 more Smart Citations
“…The Mn1-O bond lengths are in agreement with distances reported earlier for similar coordination environments. [18] The coordination angles, ranging from 86.02 (13) to 93.98(13)°( see Table 2), are close to 90°, the ideal value for a perfect octahedron. Mn1 is bridged to Mn2 and to its symmetryrelated counterpart Mn2a [the distance Mn1-Mn2 is 3.6024(10) Å], generating a trinuclear cluster.…”
Section: [Mn 3 (Atpa) 3 (Dmf) 4 ] (2)mentioning
confidence: 61%
“…Two of these MOFs (compounds 1 and 3, see below) have been separately reported; [11][12][13] therefore, their structures were not compared to each other. H 2 tpa is well known in the area of MOF chemistry [14] and has been extensively used.…”
Section: Description Of the Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on ED related to intermolecular interactions and crystal engineering is large, and we will therefore focus on host–guest structures with relation to storage or sensing of molecules. In these materials, especially calculations of the electrostatic potential (EP) and electric field (EF) in void spaces based on the MM are of great interest as in the example of the coordination polymer above, since it directly relates to the inclusion properties.…”
Section: Materials Classesmentioning
confidence: 99%
“…The design and synthesis of metal-organic frameworks constructed from transition metal ions and 1,4-benzenedicarboxylic acid (1, ligand have attracted intensive attention in recent years because of their intriguing structural topologies and tailor-made applications as functional solid materials [1][2][3]. Recent studies have shown the remarkable analogy of 1,4-BDC-type ligands with bulky methyl [4], fluorine [5], chlorine [6] or bromine [7] groups, since they not only provide astonishing thermal and chemical stability and stereo-chemical characteristics, but also prevent interpenetration phenomena of resultant polymeric networks.…”
Section: Discussionmentioning
confidence: 99%